Investigations on Mechanisms of Abrasive Particle Stress (ABSTRACT PAGE) - H. Z. Kuyumcu; L. Rolf; M. Salas (International Mineral Processing Congress, 2003)
"Industrial use of abrasive stress takes place in the area of fine grinding and in order to clean surface contaminated soil particles. Also, at many mechanical operations abrasion emerge as an unintended side effect. At the Institute for Raw and Waste Material Processing at the Technical University of Berlin systematic investigations are carried out, to further the knowledge regarding the dependence of abrasion process on material properties and stress mechanisms as a basis for design and optimisation of the process or for its avoidance. Aim was the mathematical description of the abrasion process running with a single particle stress. For the purpose of investigations an agitation cell was used. Limestone served as material.In the presented work the influence of particle diameter, particle shape and collision energy on the mass and particle size distribution of abrasion debris was studied. The surface geometry of the particle was characterised by the particle shape factor ?x and the particle diameter dp. The particle shape factor ?x stays in direct relation with the abrasion degree x, and can be substituted by a mathematical function of x.Physically the particle shape factor ?x can be interpreted as a proportion of abrasive stresses splitting up complete crystals and crystal fragments. These two different mechanisms depend on different ratios of curvature of the surface of the stressed particle. The abrasive stress of strongly curved surface areas leads to separation of complete crystals. The abrasive stress of weakly curved surface areas leads to separation of crystals fragments. Accordingly the mass of wear mAb and median diameter of the abrasion debris d50 are different. The derived mathematical relations consider this behaviour by the particle shape factor ?x , which represents the ratio of the mixture of both stress mechanisms. The dependence of the particle shape factor ?x on the abrasion degree x with an exponent approximately to 2/3 points out that the particle shape factor ?x represents a surface area relation."